Precipitation versus temperature as phenology controls in drylands - Currier, Courtney M.; Sala, Osvaldo E. (Ecology (Durham), 2022)
Cycles of plant growth, termed phenology, are tightly linked to environmental controls. The length of time spent growing, bounded by the start and end of season, is an important determinant of the global carbon, water, and energy balance. Much focus has been given to global warming and consequences for shifts in growing-season length in temperate regions. In conjunction with warming temperatures, altered precipitation regimes are another facet of climate change that have potentially larger consequences than temperature in dryland phenology globally. We experimentally manipulated incoming precipitation in a semiarid grassland for over a decade and recorded plant phenology at the daily scale for 7 years. We found precipitation to have a strong relationship with the timing of grass greenup and senescence but temperature had only a modest effect size on grass greenup. Pre-season drought strongly resulted in delayed grass greenup dates and shorter growing-season lengths. Spring and summer drought corresponded with earlier grass senescence, whereas higher precipitation accumulation over these seasons corresponded with delayed grass senescence. However, extremely wet conditions diluted this effect and caused a plateaued response. Deep-rooted woody shrubs showed few effects of variable precipitation or temperature on phenology and displayed consistent annual phenological timing compared with grasses. Whereas rising temperatures have already elicited phenological consequences and extended growing-season length for mid and high-latitude ecosystems, precipitation change will be the major driver of phenological change in drylands that cover 40% of the land surface with consequences for the global carbon, water, and energy balance.